Ultrasonic scattering attenuation in nodular cast iron - Santos, Mário (Strojniški vestnik, 2021)
This work evaluates the ultrasonic scattering attenuation of structures with complex scatterer distributions via experimental and simulation studies. The proposed approach uses experimental attenuation knowledge to infer the scatterer size and its concentration in the studied structures, which are important for the effective construction of simulated models. The MATLAB k-Wave toolbox has been used to implement the simulator. Several cast-iron samples have been used to demonstrate the importance of simulation in the characterization of such structures. First, the scattering attenuation was evaluated using the Truell and Papadakis models, and then the results were compared with experimental ones. Emphasis was given to the Papadakis approach because it takes into account the scatterer size distribution. It is demonstrated that both analytical models provide results that are far from the experimental ones. The developed simulator for the studied samples led to a predictive model, in which the attenuation was proportional to the fifth power of the scatterer size, and the corresponding formulation is close to the one proposed by the analytical models.
Keywords: anisotropy; anizotropija; impulzna ultrazvočna metoda; modeliranje; modelling; pulse-echo; simulacija; simulation; slabitev ultrazvoka; ultrasonic attenuation